2014
DOI: 10.1208/s12248-014-9619-2
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Particles for Oral Delivery of Peptide and Protein Drugs III — the Effect of Fed State Conditions on the In Vitro Release and Degradation of Desmopressin

Abstract: The effect of food intake on the release and degradation of peptide drugs from solid lipid particles is unknown and was therefore investigated in vitro using different fed state media in a lipolysis model. Desmopressin was used as a model peptide and incorporated into solid lipid particles consisting of trimyristin (TG14), tripalmitin (TG16), and tristearin (TG18), respectively. Fasted state and fed state media with varying phospholipid and bile salt concentrations, as well as fed state media with milk and ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The second feature, however, is essential for the emulsification and digestion of the lipid matrix by bile salts and physiological lipases, allowing the release of the drug into the intestinal environment. Glyceryl trimyristate or trimyristin (Dynasan 114) has shown a good balance between those two properties and it is, therefore, suitable for the formulation of protein-loaded SLMs for oral administration. These studies confirmed that the intestinal release of the encapsulated proteins (β-galactosidase, lysozyme, and desmopressin) depends on a lipase-mediated degradation mechanism, which is related to the lipid composition and to the fed–fasted state conditions. However, there is little data about the ability of SLMs to retain the incorporated protein after exposure to gastric media.…”
Section: Introductionmentioning
confidence: 91%
“…The second feature, however, is essential for the emulsification and digestion of the lipid matrix by bile salts and physiological lipases, allowing the release of the drug into the intestinal environment. Glyceryl trimyristate or trimyristin (Dynasan 114) has shown a good balance between those two properties and it is, therefore, suitable for the formulation of protein-loaded SLMs for oral administration. These studies confirmed that the intestinal release of the encapsulated proteins (β-galactosidase, lysozyme, and desmopressin) depends on a lipase-mediated degradation mechanism, which is related to the lipid composition and to the fed–fasted state conditions. However, there is little data about the ability of SLMs to retain the incorporated protein after exposure to gastric media.…”
Section: Introductionmentioning
confidence: 91%
“…The concentration of DDAVP was determined using HPLC with a diode-array detector (Chen et al, 2016 ). The HPLC method for DDAVP followed a previous work (Christophersen et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%